The influence of added carbon nanotubes on the properties of the carbon‐fiber‐reinforced paper‐based wet clutch friction materials. (21st April 2015) - Wang, Wen‐jing; Huang, Jian‐feng; Li, Wen‐bin; Jin, Yu‐guang; Wei, Fei
Abstract Different carbon nanotubes (CNT) content was used to investigate the influence on physical properties, microstructure, tribological behaviour and thermal endurance properties of the materials. Experimental results show that the bulk density of the specimens increase with the increase of the CNT content, and the open porosity of the samples gradually reduced, whereas the CNT content increases. When comparing the tribological properties of the specimens with different CNT content, specimens that contain 4 wt.% carbon nanotubes show the highest dynamic friction coefficient and the lowest variation coefficient of the dynamic friction coefficient. Moreover, the specimens exhibit more thermal stability and lower weight loss after adding the CNT. Copyright © 2015 John Wiley & Sons, Ltd.